Novel insights on anti-obesity potential of the miracle tree, Moringa oleifera: A systematic review - Ali Ali Redha; Simone Perna; Antonella Riva; Giovanna Petrangolini; Gabriella Peroni; Mara Nichetti; Giancarlo Iannello; Maurizio Naso; Milena Anna Faliva; Mariangela Rondanelli (Journal of Functional Foods, 2021)
Moringa oleifera (MO) has started to focus the attention of many researchers, especially in the last decade, due to its rich nutrient content and bioactive compounds that have numerous pharmaceutical potentials. In this systematic review, 36 research articles were included that explored the anti-obesity potential of MO through in-vitro and in-vivo studies. The research articles included 9 in-vitro studies, 27 in-vivo studies, and 3 clinical studies. The studies mainly focused on the extract of MO prepared using MO leaves and few studies particularly focused on MO isothiocyanates. The in-vitro studies were mainly based on 3T3-L1 cells, while the in-vivo studies involved a good range of male and female mice and rats. Only two research involved human studies. The major anti-obesity mechanisms of MO were through improving the lipid profile (levels of total cholesterol, triglycerides, low-density lipoprotein, very low-density lipoprotein, high-density lipoprotein, and high-density lipoprotein cholesterol) and body weight, regulating significant genes associated with adipogenesis, glucose uptake, insulin resistance, and hormones (such as leptin, vaspin, resistin, and insulin). The clinical trials studying the anti-obesity potential of MO on humans is limited and related to the impact of MO on body mass index, total cholesterol, low-density lipoprotein, and postprandial blood glucose only.